Characterization of cyclodextrin complexes with turmeric oleoresin - Haiyee, Zaibunnisa Abdul (Elsevier Ltd., 2008)

(untitled)
Turmeric rhizome oleoresin (TRO) was successfully solubilised in aqueous solution by forming inclusion complexes with Î²-cyclodextrin (BCD) and Î³-cyclodextrin (GCD). To investigate molecular associations of BCD and/or GCD with the oleoresin, phase solubility studies were undertaken, using 1,8-cineole (C10H18O) and ar-tumerone (C15H20O) as marker compounds to represent turmeric oleoresin. In the presence of cyclodextrins, the solubility of 1,8-cineole and ar-tumerone were enhanced. Based on the stability constant, k1:1, the GCD-complex was at least twice effective than BCD. Solid state inclusion complexes were also prepared, using kneading (K) and co-precipitation (CP) methods, and analysed using Fourier transform infrared (FTIR) spectrometry and scanning electron microscopy (SEM). The shift of C{double bond, long}O stretching to higher wavenumbers and strengthening of the Csingle bondO stretching band indicated the formation of a complex between CD and TRO. The new solid phase formed using the co-precipitation method, had a crystal structure which was completely different from the original morphology of oleoresin and cyclodextrins.